2018
DOI: 10.1103/physrevb.97.245129
|View full text |Cite
|
Sign up to set email alerts
|

Truncating the memory time in nonequilibrium dynamical mean field theory calculations

Abstract: The nonequilibrium Green's functions (NEGF) approach is a versatile theoretical tool, which allows to describe the electronic structure, spectroscopy and dynamics of strongly correlated systems. The applicability of this method is, however, limited by its considerable computational cost. Due to the treatment of the full two-time dependence of the NEGF the underlying equations of motion involve a long-lasting non-Markovian memory kernel that results in at least a 3 scaling in the number of time points . The sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 96 publications
2
33
0
Order By: Relevance
“…For example, if the retarded Green's function decays rapidly in the off-diagonal direction, we do not need to store its entries with moduli smaller than some threshold, and we can ignore them in the history sums. Though this is sometimes the case [50,51], decay in the Green's functions and self energies depends strongly on the parameter regime. On the other hand, we have found that the Green's functions and self energies for many systems of physical interest display a smoothness property which leads to data sparsity; they have numerically low rank off-diagonal blocks.…”
Section: A Fast Memory-efficient Methods Based On Hierarchical Low Rank Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the retarded Green's function decays rapidly in the off-diagonal direction, we do not need to store its entries with moduli smaller than some threshold, and we can ignore them in the history sums. Though this is sometimes the case [50,51], decay in the Green's functions and self energies depends strongly on the parameter regime. On the other hand, we have found that the Green's functions and self energies for many systems of physical interest display a smoothness property which leads to data sparsity; they have numerically low rank off-diagonal blocks.…”
Section: A Fast Memory-efficient Methods Based On Hierarchical Low Rank Compressionmentioning
confidence: 99%
“…51], high-order time stepping and quadrature rules [22], parallelization [49,52], and direct Monte Carlo sampling at long times [38,40]. Of these, only the memory truncation methods succeed in systematically reducing the asymptotic cost and memory complexity, but these are restricted to specific parameter regimes in which the Green's functions are numerically sparse [50,51]. Another alternative is to approximate the full propagation scheme with quantum kinetic equations or their generalizations, like the generalized Kadanoff-Baym ansatz (GKBA) [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Note that we are using the term "free" in the sense of non-interacting. External fields coupling with the particles are included in the definition of G −1 Q , but interactions are left into the action term S I , equation (11). Our goal here is to find the direct GFs by inverting the matrices G −1 Q .…”
Section: Derivation Of the General Formulamentioning
confidence: 99%
“…For instance, the formation and stability of (Bi-)Polarons is a central problem and considerable effort has been taken for its investigation [6][7][8][9][10][11][12][13][14][15]. A broad class of different methods such as quantum Monte Carlo [16,17], density-functional theory [18], density-matrix embedding theory [19], or dynamical mean-field theory [20][21][22] has been explored to study its various aspects. Evidently, the task to numerically describe such low-dimensional, strongly-correlated quantum systems has been subject to a vast development.…”
Section: Introductionmentioning
confidence: 99%